Top down : reimagining set-in sleeve design - Doherty, Elizabeth (Fashion designer) (Quince & Co, 2015)
Learn how to knit sweaters with a technique that takes classic set-in sleeve sweater construction and turns it on its head, by working seamlessly from the top down.